ANALISIS BAHASA KIASAN YANG DIGUNAKAN DALAM FILM “THE ADVENTURE OF TOM SAWYER” - Ricky, Ricky; Ambalegin, Ambalegin; Arianto, Tomi (Asosiasi Ide Bahasa Kepri, 2024)
Movies are popular forms of entertainment for younger individuals and a useful instruments for language learning. This study focuses on semantics, specifically the use of metaphorical language in the film